Assessment and Management of Cognitive and Psychosocial Difficulties for People with Multiple Sclerosis in Ireland: A National Survey of Clinical Practice - Sinéad M. Hynes; Fiadhnait O’Keeffe; Eimear Bane; Megan H. Oglesby; Christopher P. Dwyer; Robert Joyce; Olga A. Klein (International Journal of Clinical Practice)
Background. A recent survey of 109 healthcare professionals explored how UK healthcare professionals typically assess and treat multiple sclerosis (MS)-related cognitive impairment. Little is currently known about what constitutes usual care for cognitive impairment and psychosocial care for people with MS in Ireland. Aim. The aim of the current research was to survey healthcare professionals (HCPs) who work with people with MS, to understand current assessment and management of cognition and psychosocial care in people with MS in the Republic of Ireland. Methods. A cross-sectional survey design was used. Data were collected online through Microsoft forms and through postal responses. The original UK questionnaire was adapted, piloted, and distributed to Irish HCPs. Participants were qualified HCPs who work clinically with people with MS in the Republic of Ireland. Results. Ninety-eight HCPs completed the survey. Only 34% of those surveyed reported routine screening of cognition for people with MS within their services; approximately, 36% HCPs reported that they did not provide information or services in relation to cognition to people with MS and 39% reported not referring elsewhere when cognitive difficulties were suspected. Out of the 98 HCPs, 47% reported assessing mood difficulties as part of their services, with 14% unsure. In total, 70% of participants reported onward referral took place if mood difficulties were identified. The Montreal Cognitive Assessment was the most commonly administrated cognitive assessment. Cognitive intervention choices were found to be guided by clinical judgement in 75.5% of cases. Discussion. Despite the high importance placed on cognitive and psychosocial care, there is very little consistency in treatment and assessment across services for people with MS in Ireland.